Adolescent Perceptions of Climate Change on the Outskirts of the Nusantara Capital City - Very Julianto; Indra Yohanes Kiling; Meygi Pramana Lukitasari; Hanum Hanindita Priyono; Nabila Hukma Aqila; Muhammad Abidzar Syaddad; Ida Fitrina; Lubna Riyu Azharani (Utan Kayu Publishing, 2026)
Climate change is a global issue that has a widespread impact on human life. This impact is felt in almost all countries, including Indonesia, which has vulnerable geographical and geological conditions. Among the younger generation affected by climate change, adolescents occupy an important position as a vulnerable group with great potential in facing changing environmental dynamics. Based on this, this study aims to determine how adolescents on the outskirts of the Nusantara Capital City (IKN) perceive climate change. This study uses a qualitative research design. Data were collected using the photovoice technique, in which photographs and adolescents’ explanations were analyzed in an integrated manner using thematic analysis. The results of this study indicate that adolescents on the outskirts of the Nusantara Capital City (IKN) have reflective perceptions of climate change, which are formed through direct experience and supported by their cognitive development. Their environmental awareness not only encourages adaptive behavioral changes at the personal level, but also provides space for adolescents to express their opinions and propose solutions to environmental problems around them. ABSTRAK Perubahan iklim merupakan masalah global yang memiliki dampak luas terhadap kehidupan manusia. Dampak ini dirasakan di hampir semua negara, termasuk Indonesia yang memiliki kondisi geografis dan geologis yang rentan. Di antara generasi muda yang terdampak perubahan iklim, remaja menempati posisi penting sebagai kelompok yang rentan namun memiliki potensi besar dalam menghadapi dinamika lingkungan yang berubah. Berdasarkan hal tersebut, studi ini bertujuan untuk mengetahui bagaimana persepsi remaja di pinggiran Ibu Kota Nusantara (IKN) tentang perubahan iklim. Studi ini menggunakan methods approach dengan desain kualitatif. Data dikumpulkan menggunakan teknik photovoice, di mana foto dan penjelasan remaja dianalisis secara terintegrasi menggunakan analisis tematik. Hasil penelitian ini menunjukkan bahwa remaja di pinggiran Kota Ibu Kota Nusantara (IKN) memiliki persepsi yang reflektif terhadap perubahan iklim, yang terbentuk melalui pengalaman langsung dan didukung oleh perkembangan kognitif mereka. Kesadaran lingkungan mereka tidak hanya mendorong perubahan perilaku adaptif pada tingkat pribadi, tetapi juga memberikan ruang bagi remaja untuk mengemukakan pendapat dan mengusulkan solusi terhadap masalah lingkungan di sekitar mereka.